The Effect of Oral Midazolam and Chloral Hydrate Before Echocardiography in Pediatric Patients: A Randomized Double-Blind Clinical Trial - Forod Salehi MD; Hamid Reza Riasi MD; Ali Ebrahimzadeh MD; Sima Askari Janatabadi MD (SAGE Publishing, 2017)
This study aimed to compare the effects of oral midazolam and chloral hydrate in pre-echocardiography sedation of children. In this double-blind clinical trial, 68 children were randomly assigned to midazolam (0.2 mg/kg) or chloral hydrate (50 mg/kg). The intensity, duration, and onset of the drugs' effects were assessed. Data were analyzed using the χ 2 and Mann-Whitney tests ( P ≤ .05). The average onset and duration of sedation in the children assigned to midazolam was shorter than in those assigned chloral hydrate (6.35 ± 3.65 and 19.14 ± 5.86 minutes, P = .0001, and 27.64 ± 8.34 and 48.97 ± 14.81 minutes, P = .0001). Gastrointestinal side effects were more frequent in the chloral hydrate group (23.5% against 0%, P = .003). According to the results of the present study, chloral hydrate and midazolam can be appropriate choices for pre-echocardiography sedation of patients without cardiovascular risk factors. Considering the similar effectiveness, more rapid onset, and shorter duration of sedation, besides less side effects in the midazolam group, researchers recommend the routine use of this drug.